Bulaga IPS Model for Cooperative Learning - Fahri Firmansyah; Kartiningsih; Muhammad Iqbal N; Yayan Sudrajat (Journal of Instructional Development, Innovation, and Evaluation, 2023)
Over time, the learning models provided by educators to students experience diversity by modifying it in such a way as to adapt to the times. One of them is a modified cooperative learning model, namely IPS Bulaga, which was adopted from one of the television shows, ‘Eat Bulaga! Indonesia'. The method used is a qualitative method with an experimental approach that aims to see certain conditions after being influenced under controlled conditions. IPS Bulaga can be used in several materials on IPS subjects, one of which is Plurality material. The results of the evaluation showed that after learning with the Bulaga IPS type cooperative learning model it produced a satisfactory output, as seen from the student scores that exceeded the KKM limit.